COVID-19 waves in Africa: Effects of outbreak response and interventions - Olayinka Stephen Ilesanmi; Aanuoluwapo Adeyimika Afolabi (University of New South Wales, 2021)
'Introduction:' Public health safety measures have been advocated for towards the effective containment of COVID-19. This study aimed to assess the effects of public health safety measures (PHSM) implemented during different phases of the COVID-19 pandemic in Africa.   'Methods:' We conducted a retrospective analysis of the COVID-19 control measures implemented across Africa. We extracted and collated data on COVID-19 cases, deaths, and stringency level (SL) from online data repositories between 18 July, 2020 and 18 December, 2020 in Africa.   'Results:' In the South African region, COVID-19 cases increased when there was partial closure of work sectors (SL = 41.67), but decreased with complete closure of work sectors (SL=46.30) in South Africa. In North Africa, COVID-19 cases increased when there was limited contact tracing (SL = 23.15), but decreased with comprehensive contact tracing (SL = 75.00) in Tunisia. In West Africa, COVID-19 cases increased when there was partial school closure (SL = 50.93), but decreased with complete school closure (SL = 65.74) in Nigeria. In East Africa, COVID-19 cases increased when contact tracing was limited (SL = 28.70), but decreased with comprehensive contact tracing (SL = 51.85) in Sudan. In Central Africa, COVID-19 cases increased when there was partial school closure (SL = 43.52), but decreased with complete school closure (SL = 56.48) in Congo.   'Conclusion:' PHSM should be intensified to ensure the effective containment of COVID-19 in Africa. Evidence-based decisions should be made by policy makers and contextualized in each African country as the COVID-19 pandemic evolves.